Reverberation Mapping of High-z, High-Luminosity Quasars - Lira, Paulina; Botti, Ismael; Kaspi, Shai; Netzer, Hagai (Frontiers in Astronomy and Space Sciences, 2018)
We present Reverberation Mapping results after monitoring a sample of 17 high-z, high-luminosity quasars for more than 10 years using photometric and spectroscopic capabilities. Continuum and line emission flux variability is observed in all quasars. Using cross-correlation analysis we successfully determine lags between the variations in the continuum and broad emission lines for several sources. Here we present a highlight of our results and the determined radius–luminosity relations for Lyα and CIV.